Some strings attached : managing trade-offs with equity-based compensation at Boxrs4ALL - Oosterwijk, Alexander; Weinrich, Philipp von; Hulsink, Willem (London : Rotterdam School of Management, Erasmus University, 2019)
In October 2017, Boxrs4ALL was founded by Thom Uidriks and Spijk Geene in The Netherlands after winning national and international pitching contests. Boxrs4ALL sells men's underwear in The Netherlands online and donates a pair of underwear to Tanzanian school children for every pair sold. The mission of the social startup is to provide underwear for everyone to decrease the number of infections and sexual dysfunctions caused by not wearing underpants. By October 2019, Boxrs4ALL had already donated more than 2,500 pairs in Tanzania. Reassured by this success, the two entrepreneurs want to expand their product offering to women's underwear. Thus, the two young men are looking to recruit their first employee: Either Zoey, a friend of Thom with similar values and beliefs, or the more experienced Briana who was suggested by an investor. However, Briana requested equity to join and her motivations are less clear. Should Thom and Spijk give up equity to recruit Briana or hire Zoey for a salary?
Originally Published InOosterwijk, A., von Weinrich, P., & Hulsink, W. (2019). Some strings attached - Managing trade-offs with equity-based compensation at Boxrs4ALL. Rotterdam, Netherlands: Rotterdam School of Management, Erasmus University.
Includes bibliographical references and index.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Boxrs4ALL -- Case studies; Employee selection -- Case studies; Workers' compensation -- Case studies; Industries -- Social aspects -- Case studies